Molecular markers for genetic diversity, gene flow and genetic population structure of freshwater mussel species - Choupina, Altino (2018)
Freshwater mussel species are in global decline. Anthropogenic changes of river channels and the decrease of autochthonous fish population, the natural hosts of mussels larval stages (glochidia), are the main causes. Therefore, the conservation of mussel species depends not only on habitat conservation, but also on the availability of the fish host. In Portugal, information concerning most of the mussel species is remarkably scarce. One of the most known species, Unio pictorum is also in decline however, in the basins of the rivers Tua and Sabor (Northeast of Portugal), there is some indication of relatively large populations. The aforementioned rivers can be extremely important for this species conservation not only in Portugal, but also in the remaining Iberian Peninsula. Thus, it is important to obtain data concerning Unio pictorum bioecology (distribution, habitat requirements, population structure, genetic variability, reproductive cycle and recruitment rates), as well as the genetic variability and structure of the population. Concomitantly, information concerning fish population structure, the importance of the different fish species as “glochidia” hosts and their appropriate density to allow effective mussel recruitment, will also be assessed. The achieved data is crucial to obtain information to develop effective management measures in order to promote the conservation of this bivalve species, the conservation of autochthonous fish populations, and consequently the integrity of the river habitats.